2017
DOI: 10.1038/s41598-017-10140-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of Fgf23 or Klotho Does not Modulate Experimental Heart Hypertrophy Induced by Pressure Overload

Abstract: Left ventricular hypertrophy (LVH) ultimately leads to heart failure in conditions of increased cardiac pre- or afterload. The bone-derived phosphaturic and sodium-conserving hormone fibroblast growth factor-23 (FGF23) and its co-receptor Klotho have been implicated in the development of uremic LVH. Using transverse aortic constriction (TAC) in gene-targeted mouse models, we examine the role of Fgf23 and Klotho in cardiac hypertrophy and dysfunction induced by pressure overload. TAC profoundly increases serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 54 publications
4
62
0
Order By: Relevance
“…This concern has been founded upon the observation that hypertrophic and failing [20,23,28] hearts may directly produce FGF23, that particularly high FGF23 levels are found in patients with severe acute heart disease [38,39], and that patients chronically exposed to high FGF23 -such as patients with hypophosphatemic rickets/osteomalacia -do not regularly develop heart disease [40]. Experimentally, a direct role of FGF23 in the development of vascular calcification has largely been ruled out [41], and data on its contribution to left ventricular hypertrophy remains uncertain: even though several reports have suggested FGF23 to activate cardiomyocytes and induce their proliferation [8,9], later studies have questioned these findings [15][16][17][18][19][20]. Short-term results from CARE FOR HOMe have been published earlier [7].…”
Section: Discussion/conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…This concern has been founded upon the observation that hypertrophic and failing [20,23,28] hearts may directly produce FGF23, that particularly high FGF23 levels are found in patients with severe acute heart disease [38,39], and that patients chronically exposed to high FGF23 -such as patients with hypophosphatemic rickets/osteomalacia -do not regularly develop heart disease [40]. Experimentally, a direct role of FGF23 in the development of vascular calcification has largely been ruled out [41], and data on its contribution to left ventricular hypertrophy remains uncertain: even though several reports have suggested FGF23 to activate cardiomyocytes and induce their proliferation [8,9], later studies have questioned these findings [15][16][17][18][19][20]. Short-term results from CARE FOR HOMe have been published earlier [7].…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Despite this early enthusiasm for such novel therapeutic interventions, certain caveats have recently arisen: Experimentally, independent study groups did not unanimously confirm a cardiotoxic effect of FGF23 [15][16][17][18][19], and latest rodent studies have implied that FGF23 may be a consequence rather than a cause of myocardial disease [20]. Epidemiologically, the majority of cohort studies that suggested an independent role of plasma FGF23 to predict adverse cardiovascular outcome dates back several years [3][4][5]7], when our understanding of FGF23 regulation was less comprehensive.…”
Section: Strength Of Fibroblast Growth Factor 23 As a Cardiovascular mentioning
confidence: 99%
“…Neonatal cardiomyocytes treated with angiotensin II to induce cellular hypertrophy showed a smaller cell area and decreased β‐myosin heavy chain (βMHC) expression in the presence of klotho, supporting the idea that it protects against cardiac damage related to hypertrophy . However, no differences in hypertrophy were observed between klotho‐deficient mouse and wild‐type mice in a TAC model of cardiac hypertrophy …”
Section: The Nonclassical Mineral Metabolism Components Fgf‐23 and Klmentioning
confidence: 79%
“…Studies using experimental models of direct cardiac damage have been very useful to test whether FGF‐23 is a pathophysiological factor causally linked to progression of cardiac dysfunction. Thus, transverse aortic constriction (TAC) in wild‐type mice, an experimental model of pressure overload‐induced cardiac hypertrophy, induced a strong increase in serum FGF‐23 levels that was accompanied by upregulation of cardiac but not bone FGF‐23 expression, demonstrating that the heart per se is able to express FGF‐23 under pressure overload conditions . Interestingly, the same study showed that TAC‐induced cardiac hypertrophy also developed in FGF‐23 knockout mice, indicating that FGF‐23 may not be an essential factor mediating pressure‐induced cardiac hypertrophy.…”
Section: The Nonclassical Mineral Metabolism Components Fgf‐23 and Klmentioning
confidence: 99%
“…Indeed it has been long argued that the increases in FGF23 are causal for cardiac hypertrophy, although via Klotho‐independent processes. However, recent studies using mouse models of FGF23 knockout and upregulation do not support this supposition, and individuals with primarily FGF23‐related hypophosphatemic bone disease do not consistently present with ventricular hypertrophy . As with CKD, the difference may be due to whether elevations of FGF23 are occurring during hyperphosphatemia or hypophosphatemia.…”
Section: Fgf23 Chronic Kidney Disease and Cardiac Hypertrophymentioning
confidence: 99%